OSL dating of beach ridges of Dali Lake and reconstruction of hydrological parameters - Han, Zhiyong (PANGAEA, 2019)
In this study, we utilize a closed lake with well-dated lake beach ridges located on the East Asian summer monsoon margin, a region highly sensitive to monsoon precipitation changes, to obtain a temporal sequence of water volume in North China. The elevation of each beach ridge calibrated to the modern lake level was surveyed. Optically Stimulated Luminescence (OSL) dating of undisturbed sediments of beach ridges was performed. The lake area and water volume corresponding to each beach ridge were calculated using a digital elevation model (DEM).
Keywords: beach ridge; Dali Lake; digital elevation model (DEM); Holocene; lake water volume; optically stimulated luminescence (OSL)